Measurement and Perceptions of Desertification in South Africa - Hoffman, M T; Meadows, M E (Annals of Arid Zone, 2016)
This paper describes the approach and results from the first national review of desertification of South Africa. Previous studies focused on the impact of farmers on privately-owned farms along the ecotone between the arid shrublands and semi-arid grasslands in the central interior of the country. This paper draws on the perceptions of over 450 agricultural extension officers and resource conservation technicians to provide a fundamentally different picture of the problem in South Africa. A detailed description of the workshop approach used in this national review is provided. Over 34 workshops were held across the country and a standard approach was used to gather information on land tenure, land use and soil and vegetation degradation. The results show that soil erosion is perceived to be greatest in the. communal areas. especially where high levels of poverty are combined with susceptible biophysical environments. Although vegetation degradation is also highest in communal areas this relationship is not as strong as for soil erosion. The implications of these findings for the development of South Africa’s National Action Programme to Combat Desertification are discussed.